Economic impact of cultural tourism - Zrinka Zadel; Sinisa Bogdan (UTMS Journal of Economics, 2013)
The subject of analysis in the paper is economic impact of cultural tourism and identification of the main factors which directly affect cultural tourism revenues. Most countries do not have a statistical system of monitoring and analysing individual factors of cultural tourism such as the number of arrivals of cultural tourists and consumption of cultural tourists. Therefore, it is hard to assess the economic impact of cultural tourism. In cultural tourism, cultural assets are prepared and placed on the tourist market, i.e. cultural resources are transformed into cultural tourism products. The main objective is fulfilling tourists' needs, and achieving positive effects which includes economic effects. Identification of the economic impact of cultural tourism is important because cultural resources have an inestimable value for the local community. Tourism valorisation should be used in order to achieve the necessary maximum effects with minimum negative impacts which tourism may leave on cultural resources. The objective of the paper is to identify the economic contribution of cultural tourism in the Republic of Croatia and to propose a model of identification of economic impact of cultural tourism.
Keywords: L83; 330; cultural tourism product; cultural tourism; economic impact; cultural tourists